Application of nano-encapsulated olive leaf extract in controlling the oxidative stability of soybean oil. (1st January 2016) - Mohammadi, Adeleh; Jafari, Seid Mahdi; Esfanjani, Afshin Faridi; Akhavan, Sahar
Highlights: Antioxidant activity of nano-encapsulated OLE was comparable with TBHQ. Thermal stability of nano-encapsulated OLE was lower than unencapsulated OLE. Encapsulation by WPC–pectin containing 300 mg/kg OLE showed the best oil oxidative stability. Abstract: Our objective was to evaluate the antioxidant activity of olive leave extract (OLE) encapsulated by nano-emulsions in soybean oil. The average droplet size one day after production was 6.16 nm for primary W/O nano-emulsion and, 675 nm and 1443 nm for multiple emulsions stabilized by WPC alone and complex of WPC–pectin, respectively. The antioxidant activity of these emulsions containing three concentrations of 100, 200 and 300 mg OLE during storage was evaluated in soybean oil by peroxide value, TBA value and rancimat thermal stability test and was compared with blank (non-encapsulated) OLE and synthetic TBHQ antioxidant. Nano-encapsulated OLE was capable of controlling peroxide value better than unencapsulated OLE. But because of blocking phenolic compounds within dispersed emulsions droplets, thermal stability of encapsulated OLE was lower. To summarize, with increased solubility and controlled release of olive leaf phenolic compounds through their nano-encapsulation, a higher antioxidant activity was achieved.